Assessing the performance of the pedestrian path accessibility standards for people with disabilities - Nahdatunnisa, Nahdatunnisa; Tahir, M. Arzal (Universitas Mercu Buana, 2024)
An optimal pedestrian pathway should cater to various user needs, encompassing safety, comfort, and universal accessibility. This research endeavors to evaluate the efficacy of pedestrian pathways, with a particular focus on public green spaces in Kendari City. The study emphasizes the implementation of an inclusive design concept for pedestrian pathways, ensuring the protection and fulfillment of rights for all demographic groups. To achieve its objectives, the research employed both qualitative and quantitative methods. A qualitative case study approach was utilized to assess architectural elements, while a Likert scale was employed for the performance evaluation. The findings from the performance assessment indicate that the service attribute values fall short of being optimal. Observational data suggest that most existing facilities fail to adhere to universal design principles, catering to the needs of all individuals. Consequently, there is a pressing need for physical modifications in the pedestrian pathway areas. These modifications include the installation of ramps, clear markings, and pathways for people with disabilities (guiding blocks), as well as the integration of trees and plants, trash receptacles, traffic signs, and essential utilities such as street lighting and billboards. Furthermore, the research highlights the necessity of organizing street vendor (PKL) zones across all area segments to enhance overall accessibility and usability.